Injury prevention in male youth soccer: Current practices and perceptions of practitioners working at elite English academies - Read, P. J.; Jimenez, P.; Oliver, J. L.; Lloyd, R. S. (Journal of Sports Sciences, 2018)
Forty-one practitioners inclusive of physiotherapists, sports scientists and strength and conditioning coaches from the academies of elite soccer clubs in the United Kingdom completed an on-line questionnaire which examined their: (1) background information; (2) perceptions of injury occurrence and risk factors; (3) screening and return to play; and (4) approach to designing and delivering injury prevention programmes with a response rate of 55% (41/75). Contact injuries were the most common mechanism reported and players between 13-16 years of age were perceived to be at the greatest risk. Pertinent risk factors included: reduced lower limb and eccentric hamstring strength, proprioception, muscle imbalances, and under developed foundational movement skills. Joint range of motion, jump tests, the functional movement screen, overhead and single leg squats were the most utilised screening methods. Training modalities rated in order of importance included: resistance training, flexibility development, agility, plyometrics and balance training. Training frequency was most commonly once or twice per week, during warm-ups, independent sessions or a combination of both. Injury prevention strategies in this cohort appear to be logical; however, the classification of injury occurrence and application of screening tools to identify "at risk" players do not align with existing research. The frequency and type of training used may also be insufficient to elicit an appropriate stimulus to address pertinent risk factors based on current recommendations.